Enhancement of Polysulfone Ultrafiltration Membrane Performance for Produced Water Treatment by Incorporation of Graphene oxide/Chitosan/Silicon dioxide Nanocomposite - Yasir, Ahmed. T.; Alshaibi, Nadeen; Ndame, Nchwa; Hawari, Alaa H.; Benamor, Abdelbaki (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Oil and gas production is accompanied by generation of large amounts of produced water as usually three barrels of produced water is generated for each barrel of oil. Membrane-based water reclamation technologies have been applied to treat produced water. However, the presence of oil content in the produced water makes its separation very complicated due to the high affinity between oil droplets and the hydrophobic polymeric membrane. This, results in low permeate flux, low oil rejection and high irreversible fouling. In this study, graphene oxide (GO) was functionalized using chitosan (CH) to synthesize GO-CH that was further functionalized with SiO2 to produce GO-CH-SiO2 nanocomposite. Synthesized GO-CH-SiO2 was embedded in the polysulfone membrane matrix to modify the pristine Psf membrane and impart super-oleophobic properties to the membrane. Produced nanocomposites properties were characterized using XRD, FTIR and TEM analyses, while synthesized membranes were characterized for their porosity, pore size, membrane resistance and hydrophilicity. Different ratios of GO:CH were applied with a fixed SiO2 loading to produce modified membranes. Performance test for the membranes modified with 0.3wt % nanocomposite with a GO:CH ratio of (2:1) showed a 271% improvement in membrane flux compared to pristine membrane while a ratio of 1:2 (GO:CH) gave the lowest total fouling.